Optimalisasi Kader Tim Pendamping Keluarga (TPK) dengan Peningkatan Pengetahuan terkait Stunting di Kabupaten Boyolali - Wahyu Gito Putro; Hema Dewi Anggraheny; Merry Tiyas Anggraini; Endang Surani; Sri Mulyani; Vitri Widyaningsih; Ari Natalia Probandari (Jurnal Surya Masyarakat, 2024)
Stunting is still one of the priorities for a maternal and child health in Indonesia. The stunting prevalence rate in Boyolali Regency in 2023 reached 6,86%, relatively lower compared to the national level. However, the focus on handling stunting is still specifically for pregnant women and toddlers. There is a need to optimize the role of Family Support Team cadres to be able to supervise the prospective bride, as an effort to prevent stunting. This service was carried out in the Department of Population Control Service, Family Planning, Women’s Empowerment and Child Protection (DP2KBP3A) Boyolali Regency with a target of 20 family support team cadres’, who represent rom each sub-district in Boyolali Regency. The aim of this service was to increase cadres knowledge on stunting, including factors that cause stunting, pregnancy planning, and family assistance for prospective brides. The majority of cadres have completed high school education (70%), have been cadres for more than 10 years (60%), and have 1-3 jobs (60%). There was an increase in cadres’ knowledge before and after being given training (p<0,05). Result shows that activities carried out were the provision of training as an effort to complement the knowledge and understanding of family support team cadres, especially for prospective brides, was effective, demonstrated by an increase in cadres knowledge before and after training.